Pilots' perceived workload and flight performance while interacting with touchscreen inceptor during instrument landings - Zhang, Jingyi; Korek, Wojciech Tomasz; Li, Wen-Chin (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In this study, to dig into the further potential application of the touchscreen in flight operation, an integrated touchscreen system as the aircraft control inceptor was innovatively proposed. The touchscreen inceptor is integrated into the middle of the primary flight display allowing pilots to control the aircraft's movement horizontally (roll) and vertically (pitch) with their fingers. Fifty-six participants (23 pilots and 33 non-pilots) joined the Future Systems Simulator trail to perform instrument landings using the touchscreen and sidestick in conditions without and with simulated turbulence in vertical and horizontal channels. The heart rate variability reflecting the perceived workload was measured using the Inner Balance device. The flight data related to the flight path, touchdown location, and landing load were collected and calculated as the performance score. The three-way analysis of variance was applied to compare the perceived workload and flight performance between touchscreen and sidestick controllers in different disturbance conditions among pilots and nonpilots. The data analysis results indicated that in the scenario of landing with the disturbance, participants' heart rate variability was improved while interacting with the touchscreen inceptor compared to the sidestick. The flight performance of nonpilots while performing landing tasks with sidestick was significantly lower than pilots. Nevertheless, no significant difference in flight performance was found between nonpilots and pilots when using the touchscreen inceptor. The empirical study indicated that the touchscreen could provide a more intuitive interaction of a ‘point-where-you-want-to-go' control technique without the additional input device of sidestick to reduce the mental workload and cognitive stress. Furthermore, there is an evident decrease in performance score with the touchscreen inceptor compared to traditional sidestick due to the unfamiliarity of the touchscreen interactive mode in the prolonged aircraft control process. However, it is notable that nonpilots showed an equal level of flight performance with pilots in landing tasks with touchscreen control, revealing a quick-adapt interactive mode of touchscreen inceptor for novices to perform flight operations. Therefore, the training duration can be remarkably shortened for next-generation pilots, and the cost-efficiency can be improved as well.
Keywords: future flight deck; touchscreen; aircraft control; heart rate variability; flight performance